2015
DOI: 10.1080/00325481.2015.1021234
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Americans living in the United States and their risk for obesity, diabetes and kidney disease: Genetic and environmental considerations

Abstract: The Hispanic American, the largest minority population in the United States, is at increased risk for obesity, diabetes and end-stage renal disease. Here we review genetic and environmental factors that might account for their increased risk for these conditions. Whereas many environmental and genetic factors have important roles in driving the increased risk for obesity and kidney disease in this population, a case is made that excessive intake of sugary beverages is a contributory cause. Studies focusing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…The detection of perilipin A in the plasma EVs from the Hispanic (in our lean control set) with a BMI of 24 kg/m 2 suggests that elevated plasma EV perilipin A is not secondary to obesity, but rather a biomarker of adipocyte health and inflammation. Besides being close to the upper borderline of “lean” BMI, this increase may reflect metabolic dysfunction associated with the increased metabolic disease risk for Hispanics attributed in part to their genetic makeup [40]. Plasma EV perilipin A may, thus, be an obesity-independent indicator of diminished insulin sensitivity, a hypothesis that would require a larger and more comprehensive human study.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of perilipin A in the plasma EVs from the Hispanic (in our lean control set) with a BMI of 24 kg/m 2 suggests that elevated plasma EV perilipin A is not secondary to obesity, but rather a biomarker of adipocyte health and inflammation. Besides being close to the upper borderline of “lean” BMI, this increase may reflect metabolic dysfunction associated with the increased metabolic disease risk for Hispanics attributed in part to their genetic makeup [40]. Plasma EV perilipin A may, thus, be an obesity-independent indicator of diminished insulin sensitivity, a hypothesis that would require a larger and more comprehensive human study.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups, such as male adolescents (aged 12‐19 years), consumed 12% of their overall energy from these drinks . The highest intake of sugar‐sweetened beverages occurs in adolescents, young adults in their 20s, individuals with a lower socioeconomic status , and certain ethnically defined populations, including African American , Hispanic , American Indian and Alaskan Native , and Pacific peoples .…”
Section: Impact Of Liquid Sugars In Human Dietmentioning
confidence: 99%
“…This syndrome comprises a group of conditions such as diabetes, stroke, hyperlipidemia, and obesity, among others, which by themselves are prevalent in the Latino community and recognized as risk factors of AD and related dementias [48] (Table 2). Obesity and diabetes have been found to be prevalent in Latinos at alarming rates [54, 55]. Studies involving a Latino cohort in California indicated that 96% of women and 73% of men with metabolic syndrome had abdominal obesity using the conventional 102/88 cm threshold [53].…”
Section: Epidemiology Of Ad In the Latino Populationmentioning
confidence: 99%